Odpowiedzi

  • SSSJ
  • Początkujący
2010-03-30T17:31:19+02:00
A)2(x + 3) - 5 > -2x - 7
2x+6-5>-2x-7
2x+1>2x-7
2x-2x>-7-1
x>-8

b) -2(x - 1) + 5x > 7x + 12
-2x-2+5x>7x+12
-2x+5x-7x>12-5
-4x>7 /(-4)
x>1.75

d) 0,7x - 2 ≤ 0,9x - 0,1 /*10
7x-20≤ 9x-1
7x-9x≤ -1+20
-2x≤ 19 /:(-2)
x≤ -9.5



Najlepsza Odpowiedź!
2010-03-30T18:09:49+02:00
2(x + 3) - 5 > -2x - 7
2x+6-5 >-2x-7
2x+1>-2x-7
2x+2x>-7-1
4x>-8/4
x>-2

-2(x - 1) + 5x > 7x + 12
-2x+2+5x>7x+12
3x+2>7x+12
3x-7x>12-2
-4x>10/-4
x>-2 i 1/2

⅓x + 1 > -x + 2
1/3x+x>2-1
1 1/3x>1
4/3x>1
x>1/ 4/3
x>1*3/4
x>3/4

0,7x - 2 ≤ 0,9x - 0,1
0,7x-0,9x ≤ -0,1+2
-0,2x≤ 1,9/-0,2
x≤9,5

-x + 3 ≥ - ( 3x - 2 )
-x+3 ≥ -3x+2
-x+4x ≥ 2-3
3x ≥ -1÷3
x ≥ -0,3

0,1(2x - 3) < - 0,6x + 1
0,2x-0,3<-0,6x+1
0,2x+0,6x<1+0,3
0,8x<1,3÷0,8
x<1,65